Meaning of Various Social Values and Aspects in Rituals Reject the Malay Claim, Serdang, North Sumatera. - Sutikno, (International Journal of Scientific Research and Management (IJSRM), 2022)
This study examines the meaning of social values ​​and aspects in the ritual of rejecting reinforcements from the Serdang Malays, which contain many values ​​of life as well as perspectives and principles of life that are still maintained by the Serdang Malay tribal community. Values ​​are traits or things that are important and beneficial to humans, or something that perfects humans according to their nature. Values ​​can also be translated as social media or social media that are considered appropriate and useful to achieve. In the field of sociology, the existence of values ​​is very important, values ​​and aspects that influence humans in determining their choice among existing alternatives. Likewise with the values ​​and aspects contained in the ritual of rejecting reinforcements in the Malay community of Serdang, North Sumatra Province, not only as a racial tradition. ethnic Malays from the past generation, but also have very useful aspects such as social values, psychological and pedagogical values, religious values, intellectual values ​​and intelligence. This study uses descriptive qualitative methods with the techniques of observation, in-depth interviews and literacy studies. As for what makes the Malay community of Serdang still maintain the ritual of rejecting reinforcements because it is still considered to have a role and function as well as life values ​​that are still relevant and dynamic which until now continue to be continued and remain as a reference. Of course, these values ​​and aspects have advantages and disadvantages to be applied. Values ​​and aspects that have weaknesses need to find new solutions and creativity in dealing with these matters. Values ​​and aspects that have advantages need to be maintained and preserved.